Development of Walking Gait Cue Stick with Laser and Stability Control for Patients with Traumatic Brain Injury - Idris, Mat Sahat; Mohd Nazrull, Syann Lesan; Mohd Azrul Hisham, Mohd Adib (Penerbit Universiti Teknologi Malaysia, 2017)
This project is about the development of a walking gait cue stick for walking gait rehabilitation purposes. In this product development, a mechatronic device with stabiliser is attached to the walking gait cue stick. A line laser marker is accompanied with a stabilizer system to stabilized the projection of the laser. Two parameters that going to be stabilize which are the yaw and roll angle of the laser marking. The result shows good stability control for yaw angle up to 4.4 cm distance variation at the angle of 0 to 90 ̊ but relatively low stability control for the roll angle from 0 to 55 ̊ with distance variation up to 8.8 cm of the projected line laser mark. This result can further enhance walking gait training using cue stick with the aid of angles stabilising system.